Self-repairing dental implant based on magnesium alloy material and preparation method thereof
By introducing Zn, Ca and Mg30Nd into magnesium alloys, solid solution and intermetallic compounds are formed, and particle diameter distribution is optimized, the corrosion problem of magnesium alloys in the oral environment is solved, the corrosion resistance and mechanical properties of dental implants are improved, and the corrosion resistance and mechanical properties of dental implants are extended. Lifespan and biocompatibility are improved.
Patent Information
- Application Number
- CN202411764801.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-12-04
AI Technical Summary
Magnesium alloys are prone to rapid corrosion in oral environments, resulting in a short service life of dental implants and cannot meet long-term needs.
By introducing specific contents of Zn, Ca and Mg30Nd into the magnesium alloy, solid solution and intermetallic compounds are formed, the formation of oxide film is promoted, and the particle diameter distribution is optimized to improve the mechanical properties and corrosion resistance of magnesium alloys.
It significantly improves the corrosion resistance and mechanical properties of magnesium alloys, extends the service life of dental implants, and provides better oral restoration and biocompatibility.
Smart Images

Figure CN119242971A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy materials, and in particular relates to a self-repairable dental implant based on magnesium alloy material and a preparation method thereof. Background Art
[0002] In recent years, with the advancement of medical technology and the improvement of people's quality of life, dental implants have gradually become an important choice in dental restorative treatment. Dental implants are usually required to have excellent biocompatibility, sufficient mechanical strength, corrosion resistance and good long-term stability. However, traditional dental implant materials such as titanium alloys and stainless steel, although they have good mechanical properties and corrosion resistance, may require secondary surgery to remove due to their non-degradability and potential biological response problems, causing inconvenience to patients. In addition, these metal implant materials are exposed to the complex chemical environment of the oral cavity for a long time, which may cause local inflammation or other complications.
[0003] As a new type of biomaterial, magnesium alloy has received extensive attention in the field of dental and other orthopedic implants in recent years due to its good biocompatibility, moderate degradation rate, light weight and high strength. Magnesium is one of the essential elements required by the human body and can participate in a variety of biochemical reactions in the human body. The magnesium ions released by magnesium alloy implants during the degradation process will not only have no harmful effects on the human body, but will help the regeneration and repair of bone tissue. Therefore, magnesium alloy-based implants can gradually degrade in the body, avoiding the problems caused by the long-term existence of traditional metal implants, such as infection, rejection, and secondary surgery for removal.
[0004] However, the main challenge for the long-term application of magnesium alloys in the oral cavity is its corrosion resistance. Since magnesium is prone to rapid corrosion in human body fluid environments, it may cause premature failure of the material and fail to meet the long-term use requirements of dental implants. To solve this problem, researchers are committed to developing magnesium alloy implants that have good biocompatibility, sufficient corrosion resistance and self-healing capabilities through alloy design, surface treatment technology and the introduction of self-healing materials.
[0005] Self-healing material technology provides new ideas for the development of magnesium alloy implants. By introducing self-healing microcapsules or coatings into magnesium alloy materials, implants can automatically repair themselves when they are corroded or mechanically damaged, thereby extending their service life. Self-healing microcapsules usually contain repair agents that can be released when cracks or corrosion occur. These repair agents react with the surrounding environment to form a new protective layer to prevent further corrosion and damage expansion. This technology has been initially applied in the fields of aerospace, automotive industry, etc., but its application in the field of biomedical implants is still in the research stage.
[0006] Therefore, the development of a self-repairable dental implant based on magnesium alloy material can not only solve the rapid corrosion problem of traditional magnesium alloy implants, but also provide a longer service life and better oral restoration effect. The introduction of this new material is expected to significantly improve the safety and stability of dental implants and provide patients with a more comfortable treatment experience. Summary of the invention
[0007] The purpose of the present invention is to provide a self-repairable dental implant based on magnesium alloy material and a preparation method thereof, so as to solve the problem that the above-mentioned magnesium alloy material has poor corrosion resistance as a self-repairable dental implant. The self-repairable dental implant prepared by the present invention not only has excellent mechanical properties, but also has good corrosion resistance, and can provide a longer service life and better oral repair effect.
[0008] In order to achieve the above object, the present invention provides the following technical solutions: The first aspect of the present invention provides a self-repairable dental implant based on a magnesium alloy material, which comprises the following raw materials in terms of mass percentage: Zn 0.5-3%, Ca 0.01-0.1%, Mg 30 Nd 0.01-0.1%, the balance is Mg and inevitable impurities, including Zn, Ca and Mg 30 The mass ratio of Nd is (30~50):1:1.
[0009] The invention introduces specific contents of Zn, Ca and Mg into the magnesium alloy. 30 Nd can improve the mechanical strength of magnesium alloy. The present invention also found that adding Zn, Ca and Mg 30 The corrosion resistance of magnesium alloys can also be improved by setting the proportion of Nd. The analysis is based on the specific content of Zn, Ca and Mg 30 The combination of Nd reaches an ideal balance point in magnesium alloys, making magnesium alloy materials have good mechanical properties. Zn can form a solid solution with Mg, and may also form intermetallic compounds with other elements, such as MgZn2. These strengthening phases can improve the hardness and strength of the alloy. Ca can also form hard points, such as Mg2Ca. Such compounds usually have a higher melting point and can exist as a strengthening phase in the alloy. In addition, Zn, Ca and Mg 30 The Mg-Zn-Ca-Mg 30 In a corrosive environment, Zn and Ca can promote the formation of a denser oxide film on the surface of Nd alloy. This oxide film can effectively prevent the direct contact between the corrosive medium and the base metal and slow down the corrosion rate.
[0010] Preferably, the particle diameter distribution of Zn is as follows by mass percentage: 50-70 μm content is 0.5-2%, 20-40 μm content is 30-40%, and 10-15 μm content is 55-80%.
[0011] Preferably, the particle diameter distribution of Ca is as follows by mass percentage: 45-55 μm content is 1-3%, 15-30 μm content is 50-60%, and 8-10 μm content is 30-45%.
[0012] Preferably, Mg 30 The particle diameter distribution of Nd is calculated by mass percentage as follows: 40-50μm content is 5-8%, 50-70μm content is 30-45%, and 50-70μm content is 50-70%.
[0013] In order to optimize the performance of magnesium alloy materials, especially to improve their corrosion resistance, the present invention combines Zn, Ca and Mg 30 The particle size distribution of the three Nd is set to improve the corrosion resistance of magnesium alloy. 30 When the particle diameter of Nd is distributed within a specific range, these elements can be more evenly distributed throughout the magnesium alloy matrix to form a fine and evenly distributed strengthening phase. Moderate particle size can help form a denser oxide film or other forms of protective layers, which can effectively block the contact between the corrosive medium and the base metal, thereby reducing the corrosion rate. Appropriate particle size can reduce the pores generated during casting or solidification, making the material denser, reducing corrosion channels, and improving corrosion resistance. The control of particle size in the present invention also helps to obtain a more uniform microstructure, which can reduce the risk of local corrosion caused by uneven composition.
[0014] The second aspect of the present invention provides a method for preparing a self-repairable dental implant based on a magnesium alloy material, comprising the following steps: (1) Melting 50-60% of Zn powder and 20-30% of Mg powder are mixed, smelted at 700-720°C under a protective atmosphere, and cooled to room temperature to obtain alloy 1; 30-40% of Ca powder and 10-15% of Mg powder are mixed, smelted at 700-720°C under a protective atmosphere, and cooled to room temperature to obtain alloy 2; Mg 30 Nd powder, alloy 1, alloy 2 and the remaining Zn powder, Ca powder and Mg powder are mixed, and smelted at 700-750°C under a protective atmosphere to obtain a molten alloy; (2) Refining Refining agents are added to the molten alloy to remove impurities; (3) Casting The refined molten alloy is semi-continuously cast in a protective atmosphere; (4) Homogenization heat treatment The alloy ingot after casting is homogenized to eliminate the component segregation inside the alloy; (5) Solution heat treatment The magnesium alloy ingot after homogenization treatment is subjected to solution heat treatment; (6) Plastic processing Extruding the magnesium alloy ingot after solution heat treatment; (7) Timeliness treatment Performing aging treatment on the extruded alloy material; (8) Machining The alloy material after aging treatment is machined according to the shape of the dental implant to obtain a self-repairable dental implant.
[0015] In the preparation process of the present invention, zinc powder and calcium powder are added step by step, and part of the zinc powder or calcium powder is first mixed with magnesium powder to form an alloy, and then the alloy is continued to be mixed with the remaining zinc powder, calcium powder, magnesium powder and neodymium powder. 30 The addition of Nd can promote the formation of a more uniform and dense oxide film or other protective layer, thereby improving the corrosion resistance of the magnesium alloy. The invention controls the addition of these elements and can also optimize the microstructure of the alloy, improve the hardness, strength and toughness of the material, making it more suitable for dental implant applications.
[0016] Preferably, in step (3), the casting temperature is 680-720°C.
[0017] Preferably, in step (4), the temperature of the homogenization heat treatment is 350-420° C., and the time is 8-16 hours.
[0018] Preferably, in step (5), the temperature of the solution heat treatment is 350-420°C, the time is 8-16 hours, and the temperature of the solution heat treatment is 20-30°C higher than the temperature of the homogenization heat treatment.
[0019] In order to optimize the preparation process of magnesium alloy and further improve the corrosion resistance of magnesium alloy, the present invention sets the temperature of solution heat treatment higher than that of homogenization heat treatment. Analysis shows that higher temperature helps to eliminate micro defects formed in the casting process, such as holes, cracks, etc., thereby optimizing the microstructure of the material. The dense microstructure can reduce the chance of corrosive media entering the interior of the material and improve the corrosion resistance of the material. The present invention performs solution heat treatment at a higher temperature to promote the formation of a more stable solid solution, so that the alloy elements are fully dissolved into the magnesium matrix, and then through cooling, the state of these elements in the solid solution can be retained. In this state, the alloy elements can more effectively participate in the formation of a protective oxide film, thereby improving the corrosion resistance. If the temperature difference between solution heat treatment and homogenization heat treatment is too large, the material may become brittle and the grains may grow, resulting in a decrease in the mechanical properties and corrosion resistance of the magnesium alloy.
[0020] Preferably, in step (6), the temperature of plastic working is 350-450°C.
[0021] Preferably, in step (7), the aging treatment is carried out at a temperature of 200-250° C. and for a time of 24-60 h.
[0022] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention can significantly improve the mechanical properties of magnesium alloys by optimizing the alloy component ratio and particle size distribution. The addition of Zn and Ca can form a reinforcing phase to improve the hardness and strength of the material; 30 Nd helps to form more stable compounds, thereby increasing the toughness of the material.
[0023] 2. Magnesium alloys are prone to corrosion under physiological conditions. The present invention adds Zn, Ca and Mg 30 Nd elements and controlling their particle size distribution can effectively reduce the corrosion rate. The presence of these elements can promote the formation of a denser oxide film and prevent the corrosive medium from further eroding the base metal.
[0024] 3. The magnesium alloy of the present invention has good biocompatibility with human tissue, which makes it a potential biodegradable implant material. The magnesium alloy prepared by the present invention can not only improve mechanical and corrosion properties, but also maintain or improve its biocompatibility.
[0025] 4. The magnesium alloy implants with specific composition ratios of the present invention have a certain self-repairing ability, which means that after suffering minor damage, the material can restore some functions through its own mechanism, thereby extending the service life of the implant. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the appearance of a magnesium alloy round bar; Figure 2 This is an appearance diagram of a self-repairable dental implant; Figure 3 This is the SEM image of the magnesium alloy round rod. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1 This embodiment provides a self-repairable dental implant based on magnesium alloy material, which includes the following raw materials in terms of mass percentage: Zn 2%, Ca 0.05%, Mg 30 Nd 0.05%, the balance is Mg and inevitable impurities, including Zn, Ca and Mg 30 The mass ratio of Nd is 40:1:1.
[0029] The particle diameter distribution of Zn is calculated by mass percentage as follows: 50-70 μm content is 1%, 20-40 μm content is 35%, and 10-15 μm content is 64%.
[0030] The particle diameter distribution of Ca is calculated by mass percentage as follows: 45-55μm content is 2%, 15-30μm content is 55%, and 8-10μm content is 43%.
[0031] Mg 30 The particle diameter distribution of Nd is calculated by mass percentage as follows: 40-50μm content is 6%, 50-70μm content is 40%, and 50-70μm content is 54%.
[0032] A method for preparing a self-repairable dental implant based on magnesium alloy material comprises the following steps: (1) Melting 50% of Zn powder and 30% of Mg powder were mixed, smelted at 700°C in a protective atmosphere, and cooled to room temperature to obtain alloy 1; 30% of Ca powder by weight and 15% of Mg powder by weight were mixed, smelted at 715°C under a protective atmosphere, and cooled to room temperature to obtain alloy 2; Mg 30 Nd powder, alloy one, alloy two and the remaining Zn powder, Ca powder and Mg powder are mixed, and smelted at 735° C. under a protective atmosphere to obtain a molten alloy; (2) Refining A refining agent is added to the molten alloy to remove impurities. The refining agent is NaF, and the amount of the refining agent added is 10wt%; (3) Casting The refined molten alloy is semi-continuously cast in a protective atmosphere at a casting temperature of 700°C; (4) Homogenization heat treatment The alloy ingot after casting was homogenized to eliminate the component segregation inside the alloy. The homogenization heat treatment temperature was 390°C and the time was 10h. (5) Solution heat treatment The magnesium alloy ingot after homogenization treatment is subjected to solution heat treatment at a temperature of 420°C for 12 hours. The temperature of the solution heat treatment is 20°C higher than that of the homogenization heat treatment. (6) Plastic processing The magnesium alloy ingot after solution heat treatment is extruded, and the temperature of plastic processing is 415°C; (7) Timeliness treatment The extruded alloy material was subjected to aging treatment at a temperature of 220° C. for 45 h to obtain a magnesium alloy round bar with a diameter of 12 mm. (8) Machining The magnesium alloy round rod after aging treatment is machined according to the shape of the dental implant to obtain a self-repairing dental implant. The appearance of the magnesium alloy round rod and the appearance of the self-repairing dental implant are shown in Figure 1 and Figure 2 The SEM image of magnesium alloy round rod is shown in Figure 3 .
[0033] Example 2 This embodiment provides a self-repairable dental implant based on magnesium alloy material, which includes the following raw materials in terms of mass percentage: Zn 3%, Ca 0.1%, Mg 30 Nd 0.1%, the balance is Mg and inevitable impurities, including Zn, Ca and Mg 30 The mass ratio of Nd is 30:1:1.
[0034] The particle diameter distribution of Zn is calculated by mass percentage as follows: 50-70 μm content is 0.5%, 20-40 μm content is 38%, and 10-15 μm content is 61.5%.
[0035] The particle diameter distribution of Ca is calculated by mass percentage as follows: 45-55μm content is 1.5%, 15-30μm content is 58%, and 8-10μm content is 40.5%.
[0036] Mg 30The particle diameter distribution of Nd is calculated by mass percentage as follows: 40~50μm content is 7.5%, 50~70μm content is 30.5%, and 50~70μm content is 62%.
[0037] A method for preparing a self-repairable dental implant based on magnesium alloy material comprises the following steps: (1) Melting 55% of Zn powder and 25% of Mg powder were mixed, smelted at 715°C under a protective atmosphere, and cooled to room temperature to obtain alloy 1; 35% of Ca powder and 12% of Mg powder were mixed, smelted at 720°C under a protective atmosphere, and cooled to room temperature to obtain alloy 2; Mg 30 Nd powder, alloy 1, alloy 2 and the remaining Zn powder, Ca powder and Mg powder are mixed, and smelted at 710° C. under a protective atmosphere to obtain a molten alloy; (2) Refining A refining agent is added to the molten alloy to remove impurities. The refining agent is NaF, and the amount of the refining agent added is 10wt%; (3) Casting The refined molten alloy is semi-continuously cast in a protective atmosphere at a casting temperature of 700°C; (4) Homogenization heat treatment The alloy ingot after casting was homogenized to eliminate the component segregation inside the alloy. The temperature of homogenization heat treatment was 380℃ and the time was 14h. (5) Solution heat treatment The magnesium alloy ingot after homogenization treatment is subjected to solution heat treatment at a temperature of 400°C for 15 hours. The temperature of the solution heat treatment is 20°C higher than that of the homogenization heat treatment. (6) Plastic processing The magnesium alloy ingot after solution heat treatment is extruded, and the temperature of plastic processing is 400°C; (7) Timeliness treatment The extruded alloy material was subjected to aging treatment at a temperature of 225° C. for 30 h to obtain a magnesium alloy round bar with a diameter of 12 mm. (8) Machining The magnesium alloy round rod after aging treatment is machined according to the shape of the dental implant to obtain a self-repairable dental implant.
[0038] Example 3 This embodiment provides a self-repairable dental implant based on magnesium alloy material, which includes the following raw materials in terms of mass percentage: Zn 0.5%, Ca 0.01%, Mg30 Nd 0.01%, the balance is Mg and inevitable impurities, including Zn, Ca and Mg 30 The mass ratio of Nd is 50:1:1.
[0039] The particle diameter distribution of Zn is calculated by mass percentage as follows: 50~70μm content is 1.8%, 20~40μm content is 32.5%, and 10~15μm content is 65.7%.
[0040] The particle diameter distribution of Ca is calculated by mass percentage as follows: 45~55μm content is 2.5%, 15~30μm content is 54.2%, and 8~10μm content is 43.3%.
[0041] Mg 30 The particle diameter distribution of Nd is calculated by mass percentage as follows: 40~50μm content is 5.3%, 50~70μm content is 31.5%, and 50~70μm content is 63.2%.
[0042] A method for preparing a self-repairable dental implant based on magnesium alloy material comprises the following steps: (1) Melting 60% of Zn powder and 20% of Mg powder were mixed, smelted at 718°C under a protective atmosphere, and cooled to room temperature to obtain alloy 1; 30% of Ca powder by weight and 10% of Mg powder by weight were mixed, smelted at 700°C under a protective atmosphere, and cooled to room temperature to obtain alloy 2; Mg 30 Nd powder, alloy one, alloy two and the remaining Zn powder, Ca powder and Mg powder are mixed, and smelted at 725° C. under a protective atmosphere to obtain a molten alloy; (2) Refining A refining agent is added to the molten alloy to remove impurities. The refining agent is NaF, and the amount of the refining agent added is 10wt%; (3) Casting The refined molten alloy is semi-continuously cast in a protective atmosphere at a casting temperature of 705°C; (4) Homogenization heat treatment The alloy ingot after casting was homogenized to eliminate the component segregation inside the alloy. The homogenization heat treatment temperature was 395°C and the time was 14h. (5) Solution heat treatment The magnesium alloy ingot after homogenization treatment is subjected to solution heat treatment at a temperature of 415°C for 12 hours. The temperature of the solution heat treatment is 20°C higher than that of the homogenization heat treatment. (6) Plastic processing The magnesium alloy ingot after solution heat treatment is extruded, and the temperature of plastic processing is 395°C; (7) Timeliness treatment The extruded alloy material was subjected to aging treatment at a temperature of 242° C. for 42 h to obtain a magnesium alloy round bar with a diameter of 12 mm. (8) Machining The magnesium alloy round rod after aging treatment is machined according to the shape of the dental implant to obtain a self-repairable dental implant.
[0043] Comparative Example 1 The difference between this comparative example and Example 1 is that the composition of the self-repairable dental implant is different. The self-repairable dental implant in this comparative example includes the following raw materials in terms of mass percentage: Zn 3%, Ca 0.05%, Mg 30 Nd 0.05%, the balance is Mg and inevitable impurities, including Zn, Ca and Mg 30 The mass ratio of Nd is 60:1:1.
[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that the composition of the self-repairable dental implant is different. The self-repairable dental implant in this comparative example includes the following raw materials in terms of mass percentage: Zn 2%, Ca 0.05%, Mg 30 Nd 0.1%, the balance is Mg and inevitable impurities, including Zn, Ca and Mg 30 The mass ratio of Nd is 40:1:2.
[0045] Comparative Example 3 The difference between this comparative example and Example 1 is that the composition of the self-repairable dental implant is different. The self-repairable dental implant in this comparative example includes the following raw materials in terms of mass percentage: Zn 5%, Ca 0.2%, Mg 30 Nd 0.2%, the balance is Mg and unavoidable impurities, including Zn, Ca and Mg 30 The mass ratio of Nd is 25:1:1.
[0046] Comparative Example 4 The difference between this comparative example and Example 1 is that the particle diameter distribution of Zn is as follows by mass percentage: 50-70 μm content is 40%, 20-40 μm content is 15%, and 10-15 μm content is 45%.
[0047] Comparative Example 5 The difference between this comparative example and Example 1 is that the particle diameter distribution of Ca is as follows by mass percentage: 45-55 μm content is 60%, 15-30 μm content is 20%, and 8-10 μm content is 20%.
[0048] Comparative Example 6 The difference between this comparative example and Example 1 is: Mg 30 The particle diameter distribution of Nd is calculated by mass percentage as follows: 40~50μm content is 65%, 50~70μm content is 15%, and 50~70μm content is 20%.
[0049] Comparative Example 7 The difference between this comparative example and Example 1 is that the smelting process is different. The smelting steps of this comparative example are specifically as follows: Mg 30 Nd powder, Zn powder, Ca powder and Mg powder are mixed in proportion, and smelted at 735° C. in a protective atmosphere to obtain a molten alloy.
[0050] Comparative Example 8 The difference between this comparative example and Example 1 is that the temperature of the homogenization heat treatment is 350° C., the temperature of the solution heat treatment is 420° C., and the temperature of the solution heat treatment is 70° C. higher than that of the homogenization heat treatment.
[0051] Performance Testing The ultimate compressive strength and tensile strength of the magnesium alloy round bars prepared in the examples and comparative examples were tested according to GB / T228.1-2010 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Methods", and then the magnesium alloy round bars prepared in the examples and comparative examples were immersed in Hanks solution (purchased from Shanghai Chenwei Biotechnology Co., Ltd.) for 30 days, and then their ultimate compressive strength and tensile strength were tested again. The test results are shown in Table 1.
[0052] Table 1 Performance test results
[0053] It can be seen from the above performance test results that the magnesium alloys prepared in Examples 1-3 have excellent mechanical properties and good corrosion resistance, especially the ultimate compressive strength of Example 2 is the most outstanding. This is mainly because the present invention can significantly improve the mechanical properties and corrosion resistance of the magnesium alloy by optimizing the alloy component ratio and particle size distribution.
[0054] The comparative example does not adopt the necessary technical solution, resulting in its performance being significantly worse than that of the embodiment. In comparative example 1, the amount of Zn added is changed, although its mass percentage is still within the range specified by the present invention, but the amount of Zn, Ca and Mg added is changed. 30 The mass ratio of Nd changes, and the amount of Zn added is compared with Ca and Mg. 30 As the amount of Nd added increases, it can be seen that the mechanical properties and corrosion resistance of the prepared magnesium alloys have decreased significantly, proving that Zn, Ca and Mg30 The mass ratio of Nd has an important influence on the comprehensive properties of magnesium alloys. 30 The addition of Nd leads to the increase of Zn, Ca and Mg 30 The mass ratio of Nd changes, Mg 30 The addition of Nd increased compared with that of Ca. From the results, it can be seen that the mechanical properties and corrosion resistance of the prepared magnesium alloy decreased significantly, which also proved that Zn, Ca and Mg 30 The mass ratio of Nd has an important influence on the comprehensive properties of magnesium alloys. 30 Nd is added to the magnesium alloy in a specific proportion, which has an ideal balance point, so that the mechanical properties and corrosion resistance of the magnesium alloy are comprehensively improved. 30 The addition amount of Zn, Ca and Mg in the present invention exceeds the range specified in the present invention, and the ratio of the three is also not within the range specified in the present invention. It can be seen from the results that the mechanical properties and corrosion resistance of the magnesium alloy prepared by the present invention further decrease, indicating that the mass percentage of various raw materials added and the mass percentage of Zn, Ca and Mg in the present invention are 30 The importance of limiting the mass ratio of Nd at the same time will directly affect the comprehensive properties of magnesium alloys. 30 The particle diameter distribution of Nd, as can be seen from the results, the mechanical properties and corrosion resistance of the magnesium alloy prepared therefrom are significantly reduced, indicating that the particle size of the raw materials will affect the comprehensive properties of the magnesium alloy. If the particle diameter is too large, the strengthening phase may be too coarse, affecting the toughness and plasticity of the material. At the same time, large particles may become the starting point of corrosion, resulting in aggravated local corrosion. In the process of preparing the magnesium alloy in Comparative Example 7, all raw materials are directly mixed according to the added mass percentage, and then smelted and refined. It can be seen from the results that the mechanical properties and corrosion resistance of the magnesium alloy have different degrees of decline, indicating that the addition steps of various raw materials will affect the performance of the magnesium alloy. In Comparative Example 8, the temperature of the homogenization heat treatment is changed, so that the difference between the temperature of the solution heat treatment and the temperature of the homogenization heat treatment is increased. It can be seen from the results that the mechanical properties and corrosion resistance of the magnesium alloy prepared therefrom are significantly reduced, indicating that setting a specific temperature of the solution heat treatment and the temperature of the homogenization heat treatment can improve the comprehensive properties of the magnesium alloy. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.
[0055] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a self-repairable dental implant based on magnesium alloy material, characterized in that: The following raw materials are included in terms of mass percentage: Zn 0.5-3%, Ca 0.01-0.1%, Mg 30 Nd 0.01-0.1%, the balance is Mg and inevitable impurities, including Zn, Ca and Mg 30 The mass ratio of Nd is (30~50):1:1; The preparation method comprises the following steps: (1) Melting 50-60% of Zn powder and 20-30% of Mg powder are mixed, smelted at 700-720°C under a protective atmosphere, and cooled to room temperature to obtain alloy 1; 30-40% of Ca powder and 10-15% of Mg powder are mixed, smelted at 700-720°C under a protective atmosphere, and cooled to room temperature to obtain alloy 2; Mg 30 Nd powder, alloy 1, alloy 2 and the remaining Zn powder, Ca powder and Mg powder are mixed, and smelted at 700-750°C under a protective atmosphere to obtain a molten alloy; (2) Refining Refining agents are added to the molten alloy to remove impurities; (3) Casting The refined molten alloy is semi-continuously cast in a protective atmosphere; (4) Homogenization heat treatment The alloy ingot after casting is homogenized to eliminate the component segregation inside the alloy; (5) Solution heat treatment The magnesium alloy ingot after homogenization treatment is subjected to solution heat treatment; (6) Plastic processing Extruding the magnesium alloy ingot after solution heat treatment; (7) Timeliness treatment Performing aging treatment on the extruded alloy material; (8) Machining The alloy material after aging treatment is machined according to the shape of the dental implant to obtain a self-repairable dental implant.
2. The method for preparing a self-repairable dental implant based on magnesium alloy material according to claim 1, characterized in that: The particle diameter distribution of Zn is calculated by mass percentage as follows: 50-70 μm content is 0.5-2%, 20-40 μm content is 30-40%, and 10-15 μm content is 55-80%.
3. The method for preparing a self-repairable dental implant based on magnesium alloy material according to claim 1, characterized in that: The particle diameter distribution of Ca is calculated by mass percentage as follows: 45-55μm content is 1-3%, 15-30μm content is 50-60%, and 8-10μm content is 30-45%.
4. The method for preparing a self-repairable dental implant based on magnesium alloy material according to claim 1, characterized in that: Mg 30 The particle diameter distribution of Nd is calculated by mass percentage as follows: 40-50μm content is 5-8%, 50-70μm content is 30-45%, and 50-70μm content is 50-70%.
5. The method for preparing a self-repairable dental implant based on magnesium alloy material according to claim 1, characterized in that: In step (3), the casting temperature is 680~720℃.
6. The method for preparing a self-repairable dental implant based on magnesium alloy material according to claim 1, characterized in that: In step (4), the temperature of the homogenization heat treatment is 350-420°C and the time is 8-16 hours.
7. The method for preparing a self-repairable dental implant based on magnesium alloy material according to claim 1, characterized in that: In step (5), the temperature of the solution heat treatment is 350-420°C, and the time is 8-16 hours. The temperature of the solution heat treatment is 20-30°C higher than the temperature of the homogenization heat treatment.
8. The method for preparing a self-repairable dental implant based on magnesium alloy material according to claim 1, characterized in that: In step (6), the temperature of plastic working is 350~450℃.
9. The method for preparing a self-repairable dental implant based on magnesium alloy material according to claim 1, characterized in that: In step (7), the aging treatment temperature is 200-250°C and the time is 24-60h.
10. A self-repairable dental implant based on magnesium alloy material, characterized in that: Prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A biomedical corrosion-resistant magnesium alloy and its preparation method
CN102296220A
Corrosion-resistant high strength and toughness magnesium alloy tubular product and preparation process
CN110117743A
Medical magnesium alloy material for 3D printing and preparation method of medical magnesium alloy material
CN110669971A
Biodegradable Mg-Zn-Ca-Re alloy
CN114921700A
Stress-corrosion-resistant magnesium alloy applied to field of biomedical materials as well as preparation method and application of stress-corrosion-resistant magnesium alloy
CN115679173A
